Multilayer regulatory landscape during pattern‐triggered immunity in rice. Issue 12 (8th September 2021) - Tang, Bozeng; Liu, Caiyun; Li, Zhiqiang; Zhang, Xixi; Zhou, Shaoqun; Wang, Guo‐Liang; Chen, Xiao‐Lin; Liu, Wende
Summary: Upon fungal and bacterial pathogen attack, plants launch pattern‐triggered immunity (PTI) by recognizing pathogen‐associated molecular patterns (PAMPs) to defend against pathogens. Although PTI‐mediated response has been widely studied, a systematic understanding of the reprogrammed cellular processes during PTI by multi‐omics analysis is lacking. In this study, we generated metabolome, transcriptome, proteome, ubiquitome and acetylome data to investigate rice ( Oryza sativa ) PTI responses to two PAMPs, the fungi‐derived chitin and the bacteria‐derived flg22. Integrative multi‐omics analysis uncovered convergence and divergence of rice responses to these PAMPs at multiple regulatory layers. Rice responded to chitin and flg22 in a similar manner at the transcriptome and proteome levels, but distinct at the metabolome level. We found that this was probably due to post‐translational regulation including ubiquitination and acetylation, which reshaped gene expression by modulating enzymatic activities, and possibly led to distinct metabolite profiles. We constructed regulatory atlas of metabolic pathways, including the defence‐related phenylpropanoid and flavonoid biosynthesis and linoleic acid derivative metabolism. The multi‐level regulatory network generated in this study sets the foundation for in‐depth mechanistic dissection of PTI in rice and potentially in other related poaceous crop species.